Murder being once done - Rendell, Ruth, 1930-2015 (Rendell, Ruth, 1930-2015. Inspector Wexford mystery., 1999)
Inspector Wexford is called in when the body of a young woman, strangled with her own silk scarf, turns up in the Montfort family vault in a London cemetery.